The Relationship between Student Activism and Change in the University: With Particular Reference to McGill University in the 1960s - Sheppard, Peggy (Université McGill, 1989)
Keywords: Associations étudiantes; Université McGill; Étudiants

From Tomorrow’s Elite to Young Intellectual Workers: The Search for Identity among Montreal Students, 1900-1958 - Hébert, Karine (Negotiating Identities in 19th and 20th Century Montreal, 2005)
Keywords: Université McGill; Université de Montréal; Étudiants

L'opération McGill français. Une page méconnue de l'histoire de la gauche nationaliste - Warren, Jean-Philippe (Bulletin d'histoire politique, 2008)
Keywords: Anglophones; Associations étudiantes; Francophones; Groupes populaires; Université McGill; Université de Montréal; Université du Québec à Montréal

La Crise d'octobre et le milieu universitaire montréalais - Bédard, Éric (Université de Montréal, 1997)
Keywords: Crise d'octobre; Front de Libération du Québec; Université McGill; Université Sir George Williams; Université de Montréal; Université du Québec à Montréal; Étudiants

Mothering Citizens: Elite Women in Montreal, 1890-1914 - Kirkland, Mary Elizabeth (Université McGill, 2012)
Cette thèse porte sur l'engagement social et politique de femmes de l'élite montréalaise de 1890 à 1914. Pour ce faire, j'ai réuni vingt Montréalaises issues des communautés anglophones, francophones, protestantes, catholiques et orthodoxes juives en une biographie collective qui lève le voile sur leur vie domestique, les rituels propres à leur classe sociale, leur travail philanthropique, de même que sur leur engagement au sein de la communauté locale et élargie. Cet exercice de style m'a permis de mettre en évidence l'influence des identités de genre, de race, d'ethnie, de classe et de religion de chacune sur sa conception de la société. La mise en commun des expériences de ces femmes de l'élite montréalaise révèle également que leurs préoccupations étaient plurielles et qu'elles dépassent la seule question du suffrage féminin. L'idéologie maternaliste embrassée par ces activistes traçait les jalons d'un futur meilleur, d'une ville assainie et d'une nation plus forte. Ma thèse est que les femmes constituant ce corpus combinaient leurs rôles de mères et leurs identités de citoyennes afin de se tailler une place, un cercle d'influence, dans des sphères d'activité qui leurs étaient habituellement défendues, soit les sphères sociale et politique. Pour y arriver, elles ont placé la famille au cœur de leur conception du système social et ont transposé cette vision à la communauté, à la nation et au monde. En tant qu'épouses, mères, mais aussi en tant que citoyennes, ces maternalistes croyaient qu'elles avaient un rôle important à jouer dans la transformation de la société. Le fait qu'elles aient partagé les mêmes identités sexuelle et sociale leur a permis de se rapprocher. Ces similarités, jumelées à leurs différences ethniques et religieuses leurs ont conféré une influence et un pouvoir indéniable à Montréal et au-delà. Les sources consultées révèlent que ces femmes de l'élite montréalaise étaient loin d'être passives ou contentes de rester dans l'ombre. Leur engagement politique et citoyen était conscient. Leur influence comportait néanmoins des limites qu'elles durent apprendre à repousser avec doigté. Avec le déclenchement de la Grande Guerre, les tensions cachées qui existaient entre elles s'aggravèrent et il ne fut bientôt plus possible de coopérer. La séparation de ce groupe eut pour résultat de diminuer de façon notoire le pouvoir et l'influence que ces femmes de l'élite montréalaise avaient acquis en près de vingt-cinq ans.
Keywords: Bourgeoisie; Femmes

In Quest of Emotional Gratification and Cognitive Consonance: Organized Labour and Québec Separatist Nationalism, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1997)
Keywords: Nationalisme; Travail

W.D. Lighthall: Sometime Confederation Poet, Sometime Urban Reformer - Wright, Donald A. (Université McGill, 1991)
Keywords: Lighthall, William Douw; Réformistes; Écrivains

The Confédération des syndicats nationaux, the Idea of Independence, and the Sovereigntist Movement, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1991)
Keywords: Confédération des syndicats nationaux; Nationalisme

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

The Annexation Movement of 1849-50 as Seen through the Lower Canadian Press - Mills, G. H. S. (Université McGill, 1947)
Keywords: Avenir (L'); Minerve (La); Montreal Gazette; Mouvement annexionniste

The Attitudes of the Montreal Jewish Community toward French Nationalism and Separatism - Coleman, Romalis (Université McGill, 1967)
Keywords: Francophones; Juifs; Nationalisme

Les fonctions politiques du centre culturel: La Place des Arts et la Révolution tranquille - Illien, Gildas (Université McGill, 1995)
Keywords: Place des Arts; Places publiques

Le nationalisme et le radicalisme du journal La Patrie, 1879- 1897 - Laurin, L.-Luc (Université McGill, 1973)
Keywords: Nationalisme; Patrie (La)

L'échec de la contestation au Québec depuis Borduas - Bonar, James de Gaspé (Université McGill, 1975)

Art, identité et Expo 67. L'expression du nationalisme dans les œuvres des artistes québécois du Pavillon de La Jeunesse à l'Exposition universelle de Montréal - Hellman, Michel (Université McGill, 2005)
Keywords: Expositions; Nationalisme

Columns on the March: Montreal Newspapers Interpret the Spanish Civil War, 1936-1939 - Charpentier, Marc (Université McGill, 1992)
Keywords: Canada (Le); Clarté; Devoir (Le); Illustration Nouvelle (L'); Jour (Le); Journalistes; McGill Daily; Monde ouvrier (Le); Montreal Standard; Montreal Star; Montréal-Matin; Unité (L')

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

When Nationalisms Collide: Montreal's Italian Community and the St. Léonard Crisis, 1967-1969 - D'Andrea, Giuliano E. (Université McGill, 1989)
Keywords: Italiens; Saint-Léonard (crise de)

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums